Sensitivity of the Atlantic meridional overturning circulation to surface forcing - Pillar, H (2013)
The determination of the mechanisms setting the strength and structure of the large scale circulation is a fundamental and long-standing problem in physical oceanography. In this thesis, we seek to explore the mechanisms contributing to the steady state and variability of the large scale flow, with a focus on better understanding the dynamics of the Atlantic meridional overturning circulation (AMOC). In the first part of this thesis, we explore the linear sensitivity of the monthly mean subtropical AMOC to surface fluxes of buoyancy and momentum. Our approach is to use a numerical adjoint. Key insights are provided into the memory of the AMOC to historic atmospheric forcing. We find that significant memory to wind forcing is confined to timescales of less than a year. In contrast, we identify significant memory to surface buoyancy forcing spanning multi-decadal timescales and characterised by a large scale oscillation in the sign of sensitivity between the eastern and western North Atlantic basin. An important result is that to understand the origins of seasonal variability in the modelled AMOC, we must examine the response to a multidecadal history of atmospheric forcing. In the second part of this thesis, a new tool is presented that enables a clean diagnosis of the force balance controlling the circulation regime for a Boussinesq fluid. Specifically, the tool is based on the development of the "rotational momentum" equations and sets of scalar "velocity potentials" and analogous "force functions". The latter allow the projection of all forces onto the acceleration of the vertical shears and external modes of overturning to be visualised in isolation. The rotational momentum decomposition is applied to the modelled circulation in idealised Atlantic and global configurations of the MITgcm, with a focus on elucidating the dynamics of the simulated AMOC. We discuss the key role played by the rotational buoyancy forcing right on the western boundary.